HISTORY AND CURRENT TRENDS IN THE DEVELOPMENT OF NEOLOGISMS - Yakubova Nodira Baxtiyarovn (Modern American Journals, 2025)
This article explores the historical evolution and contemporary trends in the field of neology, the study of new words and their incorporation into language. Neology reflects rapid societal changes and the constant renewal of vocabulary driven by social, technological, and communicative needs. We discuss the origins of neology as a discipline, highlight its significance in various linguistic traditions, and examine current developments, especially the prolific generation of new lexical units in the 20th and 21st centuries. The study also addresses the challenges faced by neologists and underlines the multidisciplinary nature of neology that bridges linguistics with social and cognitive sciences.
Keywords: neology, neologism, lexical innovation, language change, vocabulary expansion, linguistics, lexicography